Hybrid submerged membrane photocatalytic process - Chin, Sze Sze (2008)
A hybrid system combining low-pressure submerged membrane filtration and photocatalysis in a single module was developed. A comprehensive membrane stability protocol was devised to identify the polymeric membranes that were stable under photocatalytic process. The feasibility of operation of the submerged membrane photocatalytic reactor (SMPR) in the degradation of BPA was investigated. Different methods for controlling membrane fouling during the operation of the SMPR were compared. A new submerged membrane photocatalytic reactor (SMPR) with multiple submerged lamp sources was designed and built. Long-term operation of the SMPR was evaluated and the issues of the lifetime of TiO2, fouling control and stability of the membrane were systematically addressed. Finally, a modified continuous stirred-tank reactor (CSTR) model was used to predict the degradation of resorcinol in the new SMPR. The adequacy of the modified model in simulating steady-state concentrations for different feed concentrations and residence times was evaluated.